2016
DOI: 10.1111/acps.12647
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of trial registration and selective outcome reporting in psychotherapy randomized controlled trials

Abstract: The proportion of psychotherapy randomized controlled trials correctly registered and transparently reported is poor. Psychologists should consider the impact these results have on public confidence in reported outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 40 publications
6
32
1
Order By: Relevance
“…Thus, our findings in the addiction clinical trial literature fitted within the broader context . In addition to our previous studies, several others suggest that selective reporting of outcomes and analyses is common in clinical trials. Beyond selective outcome reporting, our study shows that a significant proportion of RCTs in our sample were registered after patient enrollment ended or were not registered at all.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, our findings in the addiction clinical trial literature fitted within the broader context . In addition to our previous studies, several others suggest that selective reporting of outcomes and analyses is common in clinical trials. Beyond selective outcome reporting, our study shows that a significant proportion of RCTs in our sample were registered after patient enrollment ended or were not registered at all.…”
Section: Discussionsupporting
confidence: 77%
“…after randomization and administration of the intervention), and approximately one in three registered trials had a major discrepancy between registration and publication. A lack of trial registration or incomplete description of outcomes in a trial registration should warrant concern given the rate of selective reporting found in our study and in previous studies . Overall, the implications of our findings center on a lack of transparency because many RCTs were not registered at all, only one RCT had a documented change to its outcomes in the published report, and a significant portion of RCTs had identifiable major discrepancies.…”
Section: Discussionmentioning
confidence: 56%
“…Even without allegiance, common problems in science are likely to apply to psychotherapy researchers; such as, the problems with outcome switching and selective reporting of studies that are not prospectively registered, enabling investigators to act as if a secondary outcome was the primary. Bradley, Rucklidge, & Mulder (2017) reviewed trials published between 2010 and 2014 in the five journals with the highest journal impact factor. Out of 112 trials, about 12% were prospectively and correctly registered.…”
Section: Allegiancementioning
confidence: 99%
“…For psychotherapy RCTs, the results were even worse. Only 24.1% were registered and 4.5% free from selective outcome reporting,8 underscoring the fact that bias is not an issue just confined to pharmaceutical industry trials.…”
Section: ‘It-work-somewhere’mentioning
confidence: 99%